PENERAPAN MEDIA PEMBELAJARAN BERBENTUK KARTU DOMINO UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIIA MTs ALKHAIRAAT KALUKUBULA PADA MATERI PERKALIAN DAN PEMBAGIAN BILANGAN BULAT - Wahyuni H. Mailili (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2018)
This study discusses the efforts to improve student learning outcomes of class VIIA MTs Alkhairaat Kalukubula on multiplication materials and division of integers. The purpose of this study is to describe the application of learning media in the form of domino card to improve student learning outcomes of class VIIA MTs alkhairaat Kalukubula on multiplication materials and division of integers. This type of research is a classroom action research using a qualitative approach. The design of this study refers to the Kemmis and Mc.Taggart model consisting of four components, namely 1) planning 2) implementation of action 3) observation and 4) reflection. Data collection techniques used are the provision of tests, interviews, observations and field notes. The instrument used is a test in the form of a description. Data collection is done in three stages, namely: (1) data reduction, (2) data presentation, and (3) drawing conclusions. The results showed, on student activity and teacher activity in learning activity in cycle I reached category of Good and cycle II very good, this can give impact to improvement result and process in learning mathematics. Result of final test analysis of cycle I obtained result of percentage of average value with student absorption reach 73,07% and classical learning completeness reach 75% percentage from 28 student. While in the final test analysis of cycle II has increased according to the observation of student and teacher activities, the percentage of the average value of absorption of students reached 84.78% with completeness of learning in a classical reach 100% percentage target of 28 students. This has shown that the application of learning media in the form of domino card can improve student learning result of grade VIIA MTs Alkhairaat Kalukubula on multiplication and distribution of integer.